AI AUTHORSHIP/INVENTORSHIP THROUGH THE LENS OF THEORETICAL JUSTIFICATIONS OF INTELLECTUAL PROPERTY RIGHTS. - Olubiyi, Ifeoluwa A.; Irumekhai, Oshobugie Suleiman (ABUAD Law Journal, 2024)
The role of intellectual property (IP) law in incentivising innovation through the protection of the creations and inventions of the human intellect cannot be overemphasized. Artificial intelligence (AI), as an emerging technology, has had a significant impact on practically all sectors of society, including the field of intellectual property law. Its impact is felt in various fields of intellectual property law, such as patents, copyrights, trademarks, designs, and image rights, among others. AI is increasingly testing the limits and provisions of national and international intellectual property laws. In recent times, the IP laws on authorship, creation, and inventorship, in particular, have been re-examined in the light of AI-generated works and the question of whether AI (a non-human entity) can be recognized as such for its creations, which are potentially protectable by IP Laws. This paper will examine the intersection of artificial intelligence (AI) and intellectual property rights. It examines whether AI authorship or inventorship can be supported by the theoretical justifications of intellectual property protection. Can these justifications be used to advance the legal recognition and protection of AI as an inventor, author or otherwise?